Impact of Earthquake on River Water Quality Parameters - Leangkim Kong; Aznah N. Anuar; Ali M. Yuzir; Faizah C. Ros; Nur F. Said; Jun Asanuma (Chemical Engineering Transactions, 2023)
Massive destruction is caused by earthquakes, including building collapse, dam damage, floods, and sewage system failure, which results in landslides and debris flows. Thirteen people died because of the Ranau, Malaysia, earthquake on 5 June 2015, which had a magnitude of 6.0. A dam failure resulted in a flash flood and landslide that swept away the river’s living organisms. A lack of clean water was caused by the loose material and debris flow clogging the treatment facility water. The in-depth study of earthquake-related water quality change is still in-bounded compared to other aspects of the literature. This study aimed to evaluate earthquake impact on river water quality. The secondary water quality measurements in Bambangan and Kimolohing of the Liwagu river were obtained from the Sabah Water Department, such as turbidity, electric conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), nitrate (NO3¯), iron (Fe), manganese (Mn), aluminum (Al), alkalinity, hardness. Daily observation is employed to analyze the variation of each parameter in 2015. Consequently, turbidity was extremely high on 17 June, followed by metal elements such as Al, Fe, and Mn. The concentration of DO declined on 17 June to 3.8 mg/L. About two weeks to two months following the earthquake, the Liwagu river’s overall water quality changed until it recovered to its initial state. However, it took more than six months to recover in other parameters, like iron and manganese. The earthquake alone did not dominate the impact; however, it altered the pollution from the existing source to the river. Therefore, researching how earthquakes affect river water quality can help us understand how parameters will react to future earthquakes and help us determine the most effective method to restore the water quality of the Liwagu river.